Identification, antioxidant and cytotoxic potentials of casticin in Vitex agnus-castus fruit from different geographical regions of Turkey - TAŞKIN, TURGUT (PHARMACOTHERAPY GROUP, 2020)
Purpose: To evaluate the antioxidant and cytotoxic effects, and casticin contents of Vitex agnus-castus (VAC) fruit extract from five geographical regions of Turkey. Methods: Casticin determination in VAC fruit extracts was performed using HPLC-DAD method. The method was validated for linearity, sensitivity, selectivity, accuracy and precision. The methanol extracts of the VAC fruits were analyzed for antioxidant effects using 2,2-diphenyl-1-picrylhydrazyl (DPPH center dot) radical scavenging capacity, metal-chelation capacity assay, radical cation scavenging capacity (ABTS(center dot+)), and total phenolic content. The cytotoxic potential of the extracts against NRK-52E and HeLa cells were determined using MTT and LDH assays. Results: The casticin content of the extracts ranged from 0.048 and 0.152 %. Total phenol content was in the range of 36.67 +/- 0.7 to 74.20 +/- 1.02 mg gallic acid equivalent (GAE)/100 mg of extracts. High-to-moderate antioxidant properties were observed in the extracts. Cytotoxicity data demonstrated that all extracts showed high cytotoxic effects on HeLa cell line when compared to the NRK-52E cell line (p < 0.05). Conclusion: These results suggest that VAC fruits (Monk's pepper fruits) from Aegean sea coasts have a potential for use in the preparation of phytopharmaceutical products.
Keywords: Vitex agnus-castus; Casticin; Antioxidant; Cytotoxic activity; Anticancer; L. FRUITS; APOPTOSIS; CELLS